Long-term results of Berlin-Frankfurt-Muenster based therapy for childhood and adolescents’ lymphoblastic lymphoma - S. S. Kulikova; S. V. Semochkin; D. V. Litvinov; E. V. Inuschkina; N. V. Myakova; K. L. Kondratchik; L. V. Baidun; D. M. Konovalov; D. A. Peregudov; L. N. Schelichova; E. V. Samochatova (Онкогематология)
Lymphoblastic lymphoma (LBL) is one of predominant childhood non-Hodgkin’s lymphoma (NHL) subtypes and consists 25—30 %.   The study purpose was to investigate outcomes in children and adolescents with LBL treated with protocol NHL-BFM-90 and 95 in the Moscow region.   58 primary patients (m–40, f–18) with T- and B-LBL were enrolled from 05. 1991 to 08. 2008 (aged 1.5–21.6 years; median 11.0 years). Fifty-two (90 %) patients were treated with ALL-like therapy protocol NHL-BFM-90 or 95 for non-B-NHL and 6 (10 %) — NHL-BFM-90 for B-NHL. The complete response (CR) rate was 94 and 83 %, respectively. 5-years event-free survival (5y-EFS) was 0.80 ± 0.06 (median of observation 4.1 years) and 0.67 ± 0.19 (5.1 years), respectively (p > 0.05). 5-years overall survival (5y-OS) was 0.85 ± 0.05 and 0.80 ± 0.06 respectively (p > 0.05). The situation without mediastinal involvement was a factor unfavorable prognosis for T-LBL: 5y-EFS — 0.56 ± 0.17 vs. 0.90 ± 0.05 (p = 0.036). Thus the NHL-BFM-90 and 95 for non-B-NHL protocols are effective therapeutic regimes for pediatric LBL and obtained long-term results are comparable with international data.